2020
DOI: 10.1021/acsomega.0c01249
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Physical and Functional Niches of FAM26F by Analyzing Its Subcellular Localization and Novel Interacting Partners

Abstract: The knowledge of a protein’s subcellular localization and interacting partners are crucial for elucidating its cellular function and associated regulatory networks. Although FAM26F (family with sequence similarity 26, member F) has been recognized as a vital player in various infections, stimulation studies, cancer, and immune pathogenesis, the precise location and function of FAM26F are not well understood. The current study is the first to focus on functional characterization of FAM26F by analyzing its subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…FAM26F, also termed as Calcium homeostasis modulator protein 6 (CALHM6), has recently been recognized as a potent innate immunity modulator, owing to its calcium homeostasis modulator domain [ 19 ]. Previously, we have demonstrated that FAM26F is functionally related to calcium-binding proteins, specifically to Thioredoxin, and it was proposed that the FAM26F expression is regulated by cytosolic calcium disturbances [ 20 ]. Likewise, the HBV expression has also been shown to be linked with disturbance in calcium homeostasis and up-regulation of ROS levels [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAM26F, also termed as Calcium homeostasis modulator protein 6 (CALHM6), has recently been recognized as a potent innate immunity modulator, owing to its calcium homeostasis modulator domain [ 19 ]. Previously, we have demonstrated that FAM26F is functionally related to calcium-binding proteins, specifically to Thioredoxin, and it was proposed that the FAM26F expression is regulated by cytosolic calcium disturbances [ 20 ]. Likewise, the HBV expression has also been shown to be linked with disturbance in calcium homeostasis and up-regulation of ROS levels [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FAM26F possesses a conserved Calcium homeostasis modulator (Ca_hom-mod) domain, hence also named as Calcium homeostasis modulator protein 6 (CALHM6) [ 19 ]. Recently, FAM26F was found to be functionally related to calcium-binding proteins, and it was proposed that the FAM26F expression is regulated by cytosolic calcium disturbances [ 20 ]. Moreover, FAM26F was identified as one of the top classifiers among 371 differentially expressed genes that were functionally linked with oxidative stress and inflammation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics can be used to forecast the structural and functional characteristics of proteins. Numerous studies explored bioinformatics approaches to understand protein sequence conservation, evolutionary relationships, functional domains, active sites, physiochemical properties, and so on ( Lagunas-Rangel, 2023 , Malik et al, 2020 , Narang et al, 2021 ). After examining the relevant literature, we could not find adequate information concerning these crucial aspects of bovine chymosin.…”
Section: Introductionmentioning
confidence: 99%